Unveiling the First Staphylococcus argenteus Infection in Portugal - Conceição, Teresa (2023)
Funding Information: This work was partially supported by FCT - Fundação para a Ciência e a Tecnologia, I.P., through MOSTMICRO-ITQB R&D Unit (UIDB/04612/2020, UIDP/04612/2020) and LS4FUTURE Associated Laboratory (LA/P/0087/2020).